The Relationship Between Reproductive Health Knowledge and Reproductive Organ Hygiene Practices Among Female Adolescents at Van Duynhoven Senior High School, Saribudolok - Rio Jenita Sipayung; Rianita Siagian (Gayaku Publisher, 2025)
Background: Adolescence is characterized by significant biological changes, including menarche among female adolescents. Inadequate knowledge of menstrual and reproductive hygiene may increase the risk of reproductive tract infections (RTIs). Therefore, improving reproductive health knowledge is essential to promote healthy hygiene behaviors among adolescent girls. Objective: This study aimed to analyze the relationship between reproductive health knowledge and reproductive organ hygiene practices among female adolescents at Van Duynhoven Senior High School, Saribudolok. Methods: This study employed a quantitative research design with a cross-sectional correlational approach. A total of 86 female students were selected using a total sampling technique. Data were collected using a structured questionnaire that had been tested for validity and reliability. Univariate analysis was used to describe respondents' characteristics, while the relationship between variables was analyzed using the Chi-square test with a significance level of 0.05. Results: The findings showed that the majority of respondents had good reproductive health knowledge (55.8%) and demonstrated positive reproductive organ hygiene practices (60.5%). Bivariate analysis revealed a statistically significant relationship between reproductive health knowledge and reproductive organ hygiene practices (p = 0.002; α < 0.05). These findings indicate that better reproductive health knowledge is associated with more positive hygiene practices among female adolescents. Conclusion: Reproductive health knowledge is significantly associated with reproductive organ hygiene practices among female adolescents. A comprehensive understanding of reproductive health contributes positively to the development of adaptive and healthy hygiene behaviors. Suggestion: Schools are encouraged to collaborate with healthcare institutions to strengthen adolescent reproductive health education programs through regular health promotion, counseling, and educational activities aimed at improving students' knowledge and promoting healthy reproductive hygiene practices.